The Recruitment of Parking Attendants as Members of Radical Religious Study Group in Indonesia - Erni Kurniati (JURNAL INDO-ISLAMIKA, 2021)
How do radical religious groups recruit new members? Why do parking attendants want to be involved in radical religious study groups? This study aims to look at the role of religious study groups (pengajian) in one of the Religious Study Councils (Majelis Taklim) in Jakarta as a place for indoctrinating radicalism to people from a lower social class. The study also aims to identify the factors and approaches to radicalization. To see the phenomenon of radicalization in parking attendants, this study uses a qualitative method with a case study approach. The participants in this study are the wives of six former members of pengajian affiliated with ISIS as well as former parking attendants in Jakarta. The results of the study show that the parking attendants and their religious study groups have a significant role in attracting and recruiting new members through employment opportunities and facilities for studying the Qur'an, as well as exclusive Islamic teaching. The changes of attitude and thought that occurred in the parking attendants after attending the pengajian can be seen in their refusal to attend Friday prayers outside their group, their attendance to the weekly study group schedule, and the physical exercise performed such as self-defense.